A STUDY ON SEASONAL VARIATION OF TREMATODE INFESTATION OF Heteropneustes fossilis IN CHAPRA, BIHAR, INDIA - KUMARI, AISHWARIYA; SAHAY, DIPTI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Fish Heteropneustes fossilis is popularly known as singhi and abundantly found in rivers, ponds and canals of Bihar. This fish species play an important role in fish market because of their high nutritional and medicinal value among human population. Parasites are causing the major health problem in freshwater fish. In result occurring economic loss to our country and also effect on human health and others fish eating animal too. This study includes seasonal variation of trematode infection in Heteropneustes fossilis during the period from September, 2016 to August, 2017. Month-wise infection rate is highest in September (100 per cent) and lowest in month of February (22.22 per cent). Seasonally, highest infection rate in rainy season followed by summer and winter season.